Estimating Efficiency of Business Ecosystem Functioning in Digital Economy - O. E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The ecosystem business-model is a rather new phenomenon, thus unified methodology of estimating its efficiency has not been formed yet. The majority of researchers focus on the fact that there is a bank in the ecosystem foundation. The article proposes to study ecosystems without binding to any concrete type of activity, for instance, banking, telecommunication, etc. The author highlights a number of aspects that should be necessarily taken into account in resolving this problem. To estimate the efficiency of ecosystem business methodology is put forward based on integral indicator, which includes the following groups of criteria in key lines: operation-synergetic, finance-investment, digital and regulatory. In each of the 4 groups the author identifies factors for estimation and underlines that they can be corrected depending on specific functioning of concrete business-ecosystem. The provided methodology can be used by management of organizations dealing with business-ecosystem building, investors, heads of ministries and departments supervising these directions in order to analyze and take steps aimed at raising the efficiency of the work.